Booker T. Washington Papers Volume 7 : 1903-4. Assistant editor, Barbara S. Kraft - Washington, Booker T., 1856-1915 (Book collections on Project MUSE., 2015)
The phenomenal impact of Booker T. Washington on his time is underscored in this volume, documenting both Washington's continuing influence upon President Theodore Roosevelt and the growing dissatisfaction of some blacks with Washington's philosophy and leadership. The letters provide social historians and laymen alike with an abundant store of information on the man many consider to be the most influential figure in black history.